Cooperation under Anarchy - Oye, Kenneth A., 1949- (Book collections on Project MUSE., 1986)
This path-breaking book offers fresh insights into a perennial problem. At times, the absence of centralized international authority precludes attainment of common goals. Yet, at other times, nations realize mutual interests through cooperation under anarchy. Drawing on a diverse set of historical cases in security and economic affairs, the contributors to this special issue of World Politics not only provide a unified explanation of the incidence of cooperation and conflict, but also suggest strategies to promote the emergence of cooperation.